2022
DOI: 10.3389/fragi.2022.949924
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of miR-34a in diabetes and frailty

Abstract: Emerging evidence has shown that microRNAs (miRNAs) play critical role in the pathogenesis of several disorders. In the present minireview, we focus our attention on the functional role of a specific miRNA, namely miR-34a, in the pathophysiology of frailty and diabetes mellitus. Based on the current literature, we speculate that this miRNA may serve as a potential biomarker of frailty in diabetic older adults. Additionally, its actions on oxidative stress might represent a druggable target to obtain new potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…This observation aligns with recent review studies, such as the one by Pasquale Mone et al. ( 20 ), which emphasized the significant role of miR-34 in regulating pancreatic islets/beta cell function in the context of diabetes. These findings shed light on the multifaceted involvement of miRNAs in diabetes research and emphasize their potential as valuable tools for understanding the pathogenesis and complications of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…This observation aligns with recent review studies, such as the one by Pasquale Mone et al. ( 20 ), which emphasized the significant role of miR-34 in regulating pancreatic islets/beta cell function in the context of diabetes. These findings shed light on the multifaceted involvement of miRNAs in diabetes research and emphasize their potential as valuable tools for understanding the pathogenesis and complications of diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…7 B), one of the major miRNA involved in insulin production. MiR-34a was associated with insulin resistance being involved in pancreatic development, as well as in the onset of T 2 D [ 98 , 102 , 103 ]. There are contradictory data regarding circulating levels of miR-34a in diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggested that endothelial dysfunction was involved in both hypertension and cognitive impairment (10,11). Several medications, such as L-arginine, empagliflozin, choline, metformin, and others, have been found to improve endothelial function and may therefore be beneficial in enhancing cognitive function (12,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%